2017
DOI: 10.1523/eneuro.0331-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Brain-Derived Neurotrophic Factor Protects Large Retinal Ganglion Cells After Optic Nerve Crush in Mice

Abstract: Brain-derived neurotrophic factor (BDNF), a neurotrophin essential for neuron survival and function, plays an important role in neuroprotection during neurodegenerative diseases. In this study, we examined whether a modest increase of retinal BDNF promotes retinal ganglion cell (RGC) survival after acute injury of the optic nerve in mice. We adopted an inducible Cre-recombinase transgenic system to up-regulate BDNF in the mouse retina and then examined RGC survival after optic nerve crush by in vivo imaging. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 33 publications
0
38
2
Order By: Relevance
“…After in vivo imaging, some animals were allowed to recover on a heating pad, and others were intracardially perfused and eyes enucleated for histological analysis. 14,15 After recovery, animals were allowed to rest for at least 1 week before undergoing visual acuity and IOP measurement.…”
Section: In Vivo Imagingmentioning
confidence: 99%
“…After in vivo imaging, some animals were allowed to recover on a heating pad, and others were intracardially perfused and eyes enucleated for histological analysis. 14,15 After recovery, animals were allowed to rest for at least 1 week before undergoing visual acuity and IOP measurement.…”
Section: In Vivo Imagingmentioning
confidence: 99%
“…Upregulation of BDNF in mouse retina plays an important role in neuroprotection; enhanced RGC survival after optic nerve crush is shown by in vivo imaging [146]. Induced adult hippocampal neurogenesis via injected P7C3 (pool 7, compound 3), a compound that enhances NPC survival and BDNF restore cognition in a 5xFAD (five AD-linked mutations expressing human amyloid protein precursor and presenilin-1 transgenes) AD mouse model [100].…”
Section: Brain-derived Neurotrophic Factor (Bdnf)mentioning
confidence: 99%
“…In more detail, it has been shown that BDNF enhances RGC survival post‐injury (Chen & Weber, ). Moreover, when BDNF is overexpressed specifically in the retinal tissue, the SMI‐32+ large soma RGCs survival is promoted since these cells are more vulnerable to acute injury post‐ONC (Feng et al, ). Finally, the combination of BDNF and the free radical scavenger S‐PBN in a rat model of ON transection, showed an increase in RGC survival but not an improvement in long‐distance axon regeneration.…”
Section: Traumatic Optic Neuropathymentioning
confidence: 99%